The Factor Price Equalisation Myth - James, S. F.; Pearce, I. F. (Review of Economic Studies, 1951)
S. F. James, I. F. Pearce; The Factor Price Equalisation Myth 1, The Review of Economic Studies, Volume 19, Issue 2, 1 January 1951, Pages 111–120, https:/